Transcarotid transcatheter aortic valve implantation: multicentre experience in France. (4th August 2017) - Folliguet, Thierry; Laurent, Nicolas; Bertram, Maxime; Zannis, Konstantinos; Elfarra, Mazen; Vanhuyse, Fabrice; Maureira, Pablo; Modine, Thomas
Abstract: OBJECTIVES: Transcatheter aortic valve implantation is a well-recognized treatment option for high-risk patients with aortic stenosis. The femoral approach is possible in 80% of cases and remains the access of choice. When this approach is not feasible, other alternative routes have been proposed such as transapical, transaortic and subclavian. Transcarotid aortic valve implantation has been proposed as another direct vascular access. Its use is relatively new and still under evaluation. METHODS: We successfully performed transcarotid aortic valve implantation in 145 consecutive patients through the left or right carotid artery in 3 different French sites over a 2-year period. Data were prospectively entered in the French transcatheter aortic valve implantation database. RESULTS: The mean age was 79.8 ± 8.7 years, with a mean logistic EuroSCORE of 20.7 ± 12.6%. The procedure was successful in all patients, and no conversion was necessary. Thirty-day survival was 93.7%, 8 (5.5%) patients presented either minor or major strokes and 1 patient had a localized asymptomatic carotid dissection. All patients were immediately extubated, and none presented respiratory complications. CONCLUSIONS: Transcarotid aortic valve implantation is a safe alternative to transfemoral transcatheter aortic valve implantation, with direct access to the aortic valve, which can be performed with limited incision.